The Experiences and Perceptions of Teachers of the Deaf Children in a South African Sign Language Class - Madisha Grace (Universitas Pendidikan Mandalika, 2023)
Since Deaf children lack the foundation of a primary language, they find it difficult to learn a second language. As a result, it is suggested that South African Sign Language[1] be taught as a first language and that the environment's dominant vocal language, such as English, be learnt as a second language, primarily through writing. This essay summarises the results of a master's degree study that looked at teachers' experiences teaching Deaf students in South Africa's Gauteng region English as a First Additional Language (EFAL) using a qualitative research design. The purpose of this study was to investigate teaching methods appropriate for Deaf youngsters. Four data collection tools were used: focus group interviews, individual interviews, observations, field notes and documentation. Interviews with four female Foundation teachers took place in semi-structured focus groups and a one-on-one session. Four female Foundation Phase teachers who utilised EFAL as a language of learning and instructed Deaf students to use Sign Language as a form of communication participated in semi-structured focus groups. One of the four teachers is Deaf. The responses of the participants were recorded and analysed. Two key themes emerged from the interview data: (1) team teaching and its advantages, and (2) the use of customised test questions. The results showed that team teaching, which pairs two competent instructors—one Deaf and the other Hearing—to give learners full access to classroom communication and learning, can improve the lack of teachers' training in teaching Deaf students. The modified assessment was found to enhance these kids' academic performance and EFAL learning.